Layanan Bimbingan Kelompok dengan Teknik Pemecahan Masalah terhadap Sikap Tegas Mahasiswa dalam Mengambil Keputusan Memilih Karier pada Mahasiswa Farmasi - Enny Fitriani; Nurasyah (Yayasan Penelitian dan Inovasi Sumatera, 2021)
The research has the objective of knowing the effect of group guidance services with problem-solving techniques on student assertiveness in making career choices. The research method used in this study is a quasi-experimental research method, where from a population of 30 people, a sample of 10 people was taken by simple random sampling. Student assertiveness in making career decisions is 59.1 and after giving group guidance services the post-test = 88.7 is obtained. This means that the average score of students' assertiveness in making decisions about choosing a career was higher after being given group guidance services than before being given group guidance services, the assertiveness of students in making decisions about choosing a career was 29.6. The results of the implementation of group guidance services with problem-solving techniques on student assertiveness have a significant positive impact on the decision to choose a career.